The TLR4-Active Morphine Metabolite Morphine-3-Glucuronide Does Not Elicit Macrophage Classical Activation In Vitro - Khabbazi, Samira; Xie, Nan; Pu, Wenjun; Goumon, Yannick; Parat, Marie-Odile (Frontiers in Pharmacology, 2016)
Macrophages are abundant in the tumor microenvironment where they adopt a pro-tumor phenotype following alternative polarization induced by paracrine factors from cancer and stromal cells. In contrast, classically activated macrophages have tumoricidal activities, such that the polarization of tumor-associated macrophages has become a novel therapeutic target. Toll-like receptor 4 engagement promotes classical activation of macrophages, and recent literature suggests TLR4 agonism to prevent metastasis and promote survival in experimental metastasis models. A growing number of studies indicate that TLR4 can respond to opioids, including the opioid receptor-inactive morphine metabolite morphine-3-glucuronide (M3G). We measured the activation of TLR4 in a reporter cell line exogenously expressing TLR4 and TLR4 co-receptors, and confirmed that M3G weakly but significantly activates TLR4. We hypothesized that M3G would promote the expression of classical activation signature genes in macrophages in vitro. We exposed mouse and human macrophage cell lines to M3G or the TLR4 activator lipopolysaccharide (LPS), alone or in combination with interferon gamma (IFN-γ). The classical macrophage activation markers tested were iNOS, CD86, IL-6 or TNF-α in RAW 264.7 cells and IL-6, IL-12, IL-23, TNF-α, CXCL10 and CXCL11 in THP1 cells. Our results show that despite exhibiting TLR4-activation ability, M3G does not elicit the expression of classical activation markers in LPS-responsive macrophages.